One-step analytical method for required reinforcement stiffness of vertical reinforced soil wall with given factor of safety on backfill soil. Issue 1 (February 2021) - Wang, Lei; Wang, Chunhai; Liu, Huabei; Hung, Ching
Abstract: The selection of geosynthetic reinforcements in the design of geosynthetic-reinforced soil (GRS) retaining walls has been based on the requirement on the long-term strength. However, the mobilized loads in the reinforcements are related to both the reinforcement stiffness and soil deformation, and the desired factor of safety may not exist in the earth structure if they are not properly considered. Therefore, it is also important to take into account the long-term reinforcement stiffness when designing GRS retaining walls. In this study, a simplistic analytical method is proposed to determine the required reinforcement stiffness with given factor of safety on the backfill soil. The method takes into account soil-reinforcement interaction, nonlinear stress-strain behavior of soil, and soil dilatancy. The reinforcement strains predicted by the proposed method were compared to those analyzed by validated nonlinear Finite Element analyses, and close agreement was obtained.